The comparative economics of financial access in gender economic inclusion - Simplice Asongu; Rexon T. Nting (African Governance and Development Institute (AGDI), 2020)
The study has investigated the comparative importance of financial access in promoting gender inclusion in African countries. Gender inclusion is proxied by the female labour participation rate while financial channels include: financial system deposits and private domestic credit. The empirical evidence is based on non-contemporary Fixed Effects regressions. In order to provide more implications on comparative relevance, the dataset is categorised into income levels (middle income versus (vs.) low income); legal origins (French civil law vs. English common law); religious domination (Islam vs. Christianity); openness to sea (coastal vs. landlocked); resource-wealth (oil-poor vs. oil-rich) and political stability (stable vs. unstable). Six main hypotheses are tested, notably, that middle income, English common law, Christianity, coastal, oil-rich and stable countries enjoy better levels of "financial access"-induced gender inclusion compared to respectively, low income, French civil law, Islam, landlocked, oil-poor and unstable countries. All six tested hypothesis are validated. This is the first study on the comparative importance of financial access in gender economic participation.
Keywords: I30; L96; O16; O55; 330; Inequality; Gender Inclusion; Financial development; Africa